Experimental study on strength and durability properties of iron scrap with flyash based concrete. (2021) - Dharmaraj, R.
Abstract: Concrete is the most universally used construction material today. As concrete dries, it shrinks and is an evitable phenomenon that routinely occurs. In this investigation an attempt has been made to study the effects of different percentage of iron scrap in concrete, by the optimum percentage getting different percentage of fly ash was added and tested. Thus addition of short randomly distributed iron scrap in concrete plays an important role in enhancing the strength. The effect of short randomly oriented fibre and strength characteristics of cement oriented fibre and strength characteristics of cement concrete with aspect ratio of 100 for different of iron scrap by volume of the specimen is considered compression, split tensile, prism, durability and Dorry's abrasion test were conducted. The use of waste steel strips produced in industrial operations in machine shops and workshops as reinforcement in concrete promises to be an exciting prospect in iron scrap concrete technology. Experimental investigations were under taken by the author to determine the behaviour of test specimen in compression and flexure. The specimens include cubes, cylinders and beams of M20 concrete with iron scrap ranging from 2.5% to 15%. From the test, it was observed that the addition of iron scrap improved the flexural strength of concrete and it is suggested as cost-effective and structurally efficient material in many Civil Engineering applications.